2011
DOI: 10.1021/ic201123x
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and Molecular Structures of the Members of the Electron Transfer Series [Cr(tbpy)3]n (n = 3+, 2+, 1+, 0): An X-ray Absorption Spectroscopic and Density Functional Theoretical Study

Abstract: The electron transfer series of complexes [Cr((t)bpy)(3)](n)(PF(6))(n) (n = 3+, 2+, 1+, 0 (1-4)) has been synthesized and the molecular structures of 1, 2, and 3 have been determined by single-crystal X-ray crystallography; the structure of 4 has been investigated using extended X-ray absorption fine structure (EXAFS) analysis. Magnetic susceptibility measurements (4-300 K) established an S = 3/2 ground state for 1, an S = 1 ground state for 2, an S = 1/2 ground state for 3, and an S = 0 ground state for 4. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

28
152
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(181 citation statements)
references
References 95 publications
28
152
1
Order By: Relevance
“…For instance, the analysis of the prepeak intensities in ligand K-edge XAS spectra of transition metal complexes (i.e., excitations from the ligand 1s to metal d orbitals) provides insights into the covalent contributions to metal-ligand bonding [40][41][42][43][44][45][46]. Another example is metal K-edge XAS, probing excitations from metal 1s to d orbitals, which can be used to assign coordination numbers [47][48][49] and to probe details of the metal-ligand bonding mechanisms [18,44,50]. Recently, we have demonstrated that the prepeaks in Fe K-edge XAS spectra of ferrocene derivatives are sensitive to subtle differences in the electronic structure at the iron atom, which are induced by substituents at the cyclopentadienyl rings, i.e., beyond the first coordination shell of the metal center [51].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the analysis of the prepeak intensities in ligand K-edge XAS spectra of transition metal complexes (i.e., excitations from the ligand 1s to metal d orbitals) provides insights into the covalent contributions to metal-ligand bonding [40][41][42][43][44][45][46]. Another example is metal K-edge XAS, probing excitations from metal 1s to d orbitals, which can be used to assign coordination numbers [47][48][49] and to probe details of the metal-ligand bonding mechanisms [18,44,50]. Recently, we have demonstrated that the prepeaks in Fe K-edge XAS spectra of ferrocene derivatives are sensitive to subtle differences in the electronic structure at the iron atom, which are induced by substituents at the cyclopentadienyl rings, i.e., beyond the first coordination shell of the metal center [51].…”
Section: Introductionmentioning
confidence: 99%
“…For example, bipyridine can coordinate to transition metals in its neutral, monoanionic, or dianionic form. 20 Detailed X-ray structural analysis has shown that the reduction of bipyridine corresponds to a successive increase in the C1−C1′ bond length by roughly 0.05 Å for each electron added.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[23] Thee nvisaged ddpd complex 1 3+ should resist ligand-centered reductions and nucleophilic attack at the metal center due to the strong electron donating power of ddpd.…”
mentioning
confidence: 99%